The influence of operating condition on acoustic emission (AE) generation during meshing of helical and spur gear - Hamzah, R. I. R.; Mba, David (Elsevier Science B.V., Amsterdam., 2009)
The application of high-frequency acoustic emission (AE) technology to condition monitoring of gears is still in its infancy. Understanding the influence of gear operating parameters on the generation of AE is essential in applying the AE technology to gear condition monitoring. This paper presents experimental findings on the influence of speed and load in generating AE for operating helical and spur gears. The experimental findings suggest that any percentage reduction in specific film thickness (gimel), a direct consequence of a change in load condition, results in a nine- and four-fold percentage change in AE rms for the spur and helical gear sets, respectively. A numerical model representing changes in AE rms with variation in load and speed under near isothermal conditions for spur and helical gears was also established. In conclusion, it is postulated that the AE technology could offer a means of measuring in situ the effectiveness of a lubricant for operational spur and helical gears thereby establishing if the correct lubricating conditions are present to ensure optimal life usage.
Keywords: Acoustic emission Condition monitoring Helical gear Spur gear elastohydrodynamic lubrication wear diagnosis